Psychometric testing of the Chinese Mandarin version of the Mental Health Inventory among Chinese patients with coronary heart disease in Mainland China. Issue 6 (1st April 2014) - Liu, Meili; Chow, Aloysius; Lau, Ying; He, Hong‐Gu; Wang, Wenru
Abstract : This study aimed to develop a Chinese Mandarin version of the Mental Health Inventory (CM:MHI). The English version MHI was translated into Chinese (simple Chinese character) using the forward‐backward translation method while establishing the semantic equivalence and content validity. A convenience sample of 204 coronary heart disease (CHD) patients was recruited to evaluate the internal consistency, concurrent validity and construct validity of the CM:MHI. Forty patients completed the CM:MHI to evaluate the test–retest reliability after 2 weeks. The CM:MHI demonstrated good semantic equivalent rate (92%) and satisfactory content validity index (0.91). The internal consistency was acceptable for total and all subscales with Cronbach's alpha greater than 0.70, with the exception of the subscale of Emotional Ties (Cronbach's alpha = 0.64). The test–retest reliability was also satisfactory with intraclass correlation coefficients higher than 0.75. The concurrent validity was acceptable with significantly strong correlations between the CM:MHI and the Chinese Mandarin versions of Short Form 36 Health survey and Hospital Anxiety and Depression Scale. Confirmatory factor analysis further supported the five‐factor structure of the CM:MHI. The CM:MHI demonstrated to be a valid and reliable measure for assessing psychological distress and well‐being in Chinese‐speaking CHD patients.